Broadband UHF RFID Passive Tag Antenna for Near-Body Applications - Santiago, A.; Costa, J. R.; Fernandes. C. A. (IEEE Antennas and Wireless Propagation Letters, 2013)
One challenge for UHF RFID passive tag design is to obtain a low-profile antenna that minimizes the influence of nearbody or attached objects without sacrificing both read range and universal UHF RFID band interoperability. A new improved design of a RFID passive tag antenna is presented that performs well near problematic surfaces (human body, liquids, metals) across most of the universal UHF RFID (840–960 MHz) band. The antenna is based on a low-profile printed configuration with slots, and it is evaluated through extensive simulations and experimental tests.